PERANAN SUPLAI ENERGI GAS BUMI TERHADAP PERTUMBUHAN INDUSTRI NASIONAL DI INDONESIA - Eman Singgih (Journal Of Communication Education, 2018)
ABSTRACTNatural gas supply to the industry is in urgent need of pipeline infrastructure, where pipelines function as distribution. Therefore, the development of the use of gasbumi to be used up to the industry makes the role of pipeline distribution becomes very important. Limited gas infrastructure is a major obstacle in terms of maximizing the use of natural gas, this has the perception that the investment of natural gas infrastructure is very expensive, so the use of gasbumi has a price that is not cheap because of the cost of expensive infrastructure. This is the problem if you want to maximize the use of gasbumi. If this problem can be solved, then the use of gas for the industrial use is very possible for the industry to grow and will bring the consequent absorption of manpower meaningfully. Keyword: gas supply, Industrial Growth.